Functional diagnosis of residual lymphomas after radiochemotherapy with positron emission tomography comparing FDG- and FLT-PET - Kasper, Bernd; Egerer, Gerlinde; Gronkowski, Martina; Haufe, Sabine; Lehnert, Thomas; Eisenhut, Michael; Mechtersheimer, Gunhild; Ho, Anthony Dick; Haberkorn, Uwe (Leukemia and lymphoma, 2007)
Positron emission tomography (PET) using 2-deoxy-2-[18F]fluoro-d-glucose (FDG) is used as a functional imaging technique for the staging and follow-up of lymphomas. However, additional information about the tumor proliferation rate using 3′-deoxy-3′-[18F]fluorothymidine (FLT) may be useful for the assessment of prognosis. We enrolled 48 patients with Hodgkin's (n = 15) and non-Hodgkin's lymphoma (n = 33) with residual masses >2 cm examined by tracer studies with FDG and FLT. The results were related to median overall and progression-free survival. In 15 out of 48 patients analysed using FDG, positive results were found. Using FLT, 10 out of 48 patients were positive. 33 patients were FDG negative. Eight patients were positive both using FDG and FLT. Overall survival for patients with a negative PET scan was significantly higher than for patients with positive PET, irrespective of the tracer used. FLT alone was able to discriminate between patients with long or short overall survival. However, there was no statistical significance comparing FDG/FLT negative versus FDG negative alone. Although FDG detected more lesions than did FLT, the additional biological characterization of tumor tissue with respect to proliferation by FLT might be useful by providing complementary information for the identification of recurrence. However, the present data show no advantage of combined FDG/FLT studies over FDG alone with respect to the prediction of survival.
Frontdoor: Published online: 01 Jul 2009
Gesehen am 22.11.2021